1975
DOI: 10.2466/pms.1975.40.3.755
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Kinesthesis through Time and after Active and Passive Movement

Abstract: The position sense of a stationary arm was investigated subsequent to an horizontally adductive movement with axis the shoulder joint. The right arm was the treated arm: it reached a test position actively, using minimal voluntary effort, or passively from each of 10 starting positons. The blind-folded S localized the index finger of the treated arm by attempting to touch it with the index finger of his left hand. The results indicate that subsequent to active movement the final position of a limb is more accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 11 publications
2
22
0
1
Order By: Relevance
“…It has been reported that the ability to determine the position of the upper limb in space tends to degrade during visual occlusion, implying that proprioception drifts when it is not calibrated by vision. 9,40 By contrast, other studies failed to reveal a deterioration in ability to estimate upper-limb location when vision was occluded. 11,12,19 In all these previous studies, position sense was assessed in the upper limbs and not in the lower limbs as in this study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been reported that the ability to determine the position of the upper limb in space tends to degrade during visual occlusion, implying that proprioception drifts when it is not calibrated by vision. 9,40 By contrast, other studies failed to reveal a deterioration in ability to estimate upper-limb location when vision was occluded. 11,12,19 In all these previous studies, position sense was assessed in the upper limbs and not in the lower limbs as in this study.…”
Section: Discussionmentioning
confidence: 83%
“…9,13,24 It is frequently measured by asking a subject to move the limb from a resting position to a reference position as rapidly as possible in response to a visual or auditory stimulus. 14,19,20,26 Two studies investigated the effect of eccentric exercise on muscle reaction time of the upper limbs after a light stimulus and produced contrasting results.…”
mentioning
confidence: 99%
“…Several studies have shown that limb position sense decays over time, even at intervals as short as a few seconds [22][23][24]. This decay could potentially improve performance in the crossed-hands condition specifically since impaired performance in this condition is due to interference from a proprioceptive signal in an external spatial reference frame.…”
Section: Resultsmentioning
confidence: 99%
“…Although this drift in position sense was insignificant for all but the 15°wrist flexion target in the first control condition, it was qualitatively present for the majority of target positions in each condition. The issue of proprioceptive drift was assessed by Wann and Ibrahim (1992) to clarify conflicting reports in the literature that either supported (Craske and Cranshaw 1975;Prablanc et al 1979) or refuted (Del Ray and Lichter 1971;Lee and Kelso 1979) the existence of a drift in the sense of limb position with visual occlusion. Wann and Ibrahim (1992) studied the capacity of subjects to correctly indicate the position of the right hand (i.e.…”
Section: Discussionmentioning
confidence: 99%